Moss layer projective vegetation cover at 56 sites in Central and Eastern Yakutia, in Summer 2021 (RU-Land_2021_Yakutia) - Schild, Laura; Kruse, Stefan; Heim, Birgit; Stieg, Amelie; von Hippel, Barbara; Gloy, Josias; Smirnikov, Viktor; Töpfer, Nils; Troeva, Elena I; Pestryakova, Luidmila A; Herzschuh, Ulrike (PANGAEA, 2023)
Moss layer projective vegetation cover is given in percent for each taxon and multiple quadrats at 57 sites with different vegetation types. The cover of different vegetation types at the sites is given in percent as well. The vegetation surveys were carried out in four different study areas in the Sakha Republic, Russia: in the mountainous region of the Verkhoyansk Range within the Oymyakonsky and Tomponsky District (Event EN21-201 - EN21-219), and in three lowland regions of Central Yakutia within the Churapchinsky, Tattinsky and the Megino-Kangalassky District (Event EN21220 - EN21264). The study area is located within the boreal forest biome that is underlain by permafrost soils. The aim was to record the projective ground vegetation in different boreal forest types studied during the RU-Land_2021_Yakutia summer field campaign in August and September 2021. The ground vegetation projective cover in percent was assessed within a circular forest plot of 15m radius. Depending on the heterogeneity of the forest plot, multiple vegetation types (VA, VB, or VC) were surveyed separately. The assignment of a vegetation type is always unique to a site. Up to four quadrats of 2x2 m were surveyed per vegetation type and projective cover in percent recorded separately for herbaceous and moss layers. All vegetation smaller than 40 cm was recorded. Additionally, ground vegetation projective cover was surveyed in 4 rings of 50 cm width around the center of the circular forest plot. Photos of quadrats were taken at the time of survey. In total, 491 quadrats at 57 forest plots were investigated. All data were collected by scientists form the Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research (AWI) Germany, the University of Potsdam Germany, and the North-Easter Federal University of Yakutsk (NEFU) Russia.
Keywords: above-ground biomass; Biomass; boreal forest; Central Yakutia; Field observation; Russia; Sakha Republic; Siberia; understory vegetation; vegetation survey; Yakutia